Sexual Assault in the Ivory Tower: Public Opinion on University Accountability and Mandatory Reporting. (April 2019) - Mancini, Christina; Pickett, Justin T.; Call, Corey; McDougle, Robyn Diehl; Brubaker, Sarah Jane; Brownstein, Henry H.
Highly publicized college sex crimes have recently captured public and policy attention. In response, greater discussion has turned to institutional accountability and controversial reforms such as mandatory reporting (MR). No study to date has measured public perceptions of campus sex assault procedures, however. This omission is notable because public opinion can directly and indirectly shape crime policy and because the topic has become increasingly politicized. Drawing on a 2015 poll of Virginia residents, this study evaluates views about campus sexual assault policy. Results indicate that two thirds of the public feel universities can effectively respond to sex crime and a large majority favors MR. Some differences in public opinion are evident. Research and policy implications are discussed.